PENGARUH SANKSI, PELAYANAN FISKUS, SOSIALISASI, DAN KESADARAN PAJAK TERHADAP KEPATUHAN WPOP - Desak Ayu Sriary Bhegawati; Anik Yuesti; I Gusti Ayu Agung Janur Ratna Sari (KRISNA: Kumpulan Riset Akuntansi, 2023)
Taxpayer compliance is a form of obedience that is done to comply with existing tax provisions and or regulations, but must be implemented in fulfilling its tax obligations. In the self-assessment system taxpayers have the freedom to calculate, deposit, self-report their tax obligations. Factors that affect taxpayer compliance include sanctions, fissure services, socialization, and tax awareness. This research is intended to comply with whether sanctions, fissure services, tax socialization, and awareness have an effect on the compliance of Private Taxpayers in KPP Pratama Denpasar Timur. The method of determining the pattern used in this test is unintentional sampling with a pattern quantity of a hundred obtained primarily based on the components Slovin. The information analysis technique used on this have a look at is a more than one linear regression analysis preceded via a classical assumption check. based on the outcomes of the evaluation executed, it modified into concluded that sanctions, fissure offerings, and tax awareness have a top notch impact at the compliance of private taxpayers at the same time as tax socialization has no vast impact at the compliance of personal taxpayers.